2018
DOI: 10.1016/j.amepre.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

The Medi-Cal Incentives to Quit Smoking Project: Impact of Statewide Outreach Through Health Channels

Abstract: Introduction:Little is known about how incentives may encourage low income smokers to call for quitline services. This study evaluates the impact of outreach through health channels on California Medicaid (Medi-Cal) quitline caller characteristics, trends, and reach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The statewide Medi-Cal Incentives To Quit Smoking project's statewide outreach through health channels was 2012 to 2015. 30 The UC quits project was a collaboration across all five University of California health systems in implementing bidirectional eReferrals during the study time period. 31,32 Reach During the study time period, 1,149 eReferrals were placed, reflecting 7.1% of 16,083 clinical encounters with a tobacco user.…”
Section: Results Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The statewide Medi-Cal Incentives To Quit Smoking project's statewide outreach through health channels was 2012 to 2015. 30 The UC quits project was a collaboration across all five University of California health systems in implementing bidirectional eReferrals during the study time period. 31,32 Reach During the study time period, 1,149 eReferrals were placed, reflecting 7.1% of 16,083 clinical encounters with a tobacco user.…”
Section: Results Implementationmentioning
confidence: 99%
“…12,26 We did not measure utilization of medications, which may improve quit rates, as these may not have been prescribed and documented in the EHR but used over the counter. There was also a concurrent Helpline offer for free nicotine patches mailed directly to patients in the Medi-Cal Incentives to Quit Smoking project (2012-2015) 30 which would also not have been documented in the EHR. We found that second eReferrals had a lower quit rate of 9.7% at 6 to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Per-caller costs for the all-household mailings were considerably lower than the $260 cost per call reported by the TIPs advertising campaign to generate calls to the national quitline. 24,25 As described in this issue by Tong et al, 19 during the MIQS project, there was a 70% increase in the average number of calls per year to the CSH from Medi-Cal members compared with periods prior to the MIQS project. MIQS outreach efforts originally sought to enroll 75,000 smokers and ended up engaging 92,900 Medi-Cal smokers.…”
Section: Medi-cal Incentives To Quit Smoking Outreach Strategiesmentioning
confidence: 96%
“…In this issue, Tong et al, 19 Vijayaraghavan and colleagues, 20 Saw et al, 21 and Dove and colleagues 22 describe various outreach strategies to low-income, American Indian, African American, Asian, Latino, white, and pregnant women/women with children populations and their impact on increasing calls to the CSH. As noted by Hood-Medland et al, 23 one of the most successful outreach methods leveraged existing "all-household" mailings to California's 14 million Medi-Cal members.…”
Section: Medi-cal Incentives To Quit Smoking Outreach Strategiesmentioning
confidence: 99%
“…However, the percentage of pregnant women who received counseling did not change and the percentage of nonpregnant women who received counseling decreased, which may have been because of the corresponding 70% increase in callers. 26 Overall, 13.6% of women who called the Helpline during the MIQS incentive period asked for the $20 financial incentive and this percentage did not differ substantially by pregnancy status, suggesting that promotion of the $20 gift cards reached both pregnant and nonpregnant women. The study also found that minority groups were more likely to ask for $20 indicating that MIQS reached a diverse population of women of reproductive age.…”
Section: Discussionmentioning
confidence: 92%